2017
DOI: 10.1016/j.trecan.2017.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in Cancer Susceptibility and Survival: More Than the Color of the Skin?

Abstract: Epidemiological studies point to race as a determining factor in cancer susceptibility. In US registries recording cancer incidence and survival by race (distinguishing “Black versus White”), individuals of African ancestry have a globally increased risk of malignancies compared to Caucasians and Asian Americans. Differences in socioeconomic status and health care access play a key role. However, the lesser disease susceptibility of Hispanic populations with comparable life-styles and socioeconomic status as A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(123 citation statements)
references
References 143 publications
0
122
0
1
Order By: Relevance
“…Some studies cited in the CDC guidelines included data from the 1980s and 1990s, 18 For example, some studies included skin cancer patients but excluded patients with other types of cancer. 22,23,27,31 Previous studies have shown that White race is associated with a higher incidence of skin cancer, 54 pain, 55 receiving opioids, 56,57 and experiencing overdose. 36 Therefore, selective inclusion of skin cancers (or selective exclusion of other cancers) could lead to selection bias, threatening both internal and external validity.…”
Section: Threats To External Validitymentioning
confidence: 99%
“…Some studies cited in the CDC guidelines included data from the 1980s and 1990s, 18 For example, some studies included skin cancer patients but excluded patients with other types of cancer. 22,23,27,31 Previous studies have shown that White race is associated with a higher incidence of skin cancer, 54 pain, 55 receiving opioids, 56,57 and experiencing overdose. 36 Therefore, selective inclusion of skin cancers (or selective exclusion of other cancers) could lead to selection bias, threatening both internal and external validity.…”
Section: Threats To External Validitymentioning
confidence: 99%
“…However, their study has a significant age difference (median age 61) compared to ours (median age 43), and did not account for racial differences in the analysis. Since both age [43] and race [44,45] play important roles in predicting cancer risk, and are related to the DNA-methylation changes in breast cancer tissues [46][47][48], our…”
Section: Discussionmentioning
confidence: 99%
“…Some of these mutational processes are related to agingassociated phenomena such as declining DNA damage repair 65,66 , somatic mosaicism and the accumulation of mutations over time 59,67,68 . However, other processes related to immune surveillance, evolutionary selection, disease aetiology and epigenetics are also likely involved [69][70][71] . In addition to such biological factors, lifestyle and socioeconomic considerations like diet 72 and microbiome composition 73 can continuously shape tumour evolution from its earlier steps.…”
Section: Discussionmentioning
confidence: 99%